Development of Human Genome Editing Tools for the Study of Genetic Variations and Gene Therapies - Yang, Luhan (Harvard University, 2013)
The human genome encodes information that instructs human development, physiology, medicine, and evolution. Massive amount of genomic data has generated an ever-growing pool of hypothesis. Genome editing, broadly defined as targeted changes to the genome, posits to deliver the promise of genomic revolution to transform basic science and personalized medicine. This thesis aims to contribute to this scientific endeavor with a particular focus on the development of effective human genome engineering tools.